Follow that dream [videorecording (DVD)] - Douglas, Gordon, 1907-1993; Presley, Elvis, 1935-1977; O'Connell, Arthur, 1908-1981; Helm, Anne, 1938-; Moore, Joanna, -1997; Powell, Richard, 1908-1999 (MGM Home Entertainment, 2012)
Elvis plays a sexy but naive country boy in this light-hearted musical comedy about a backwoods family homesteading along the Florida coast.